Severe autoimmune hemolytic anemia following receipt of SARS‐CoV‐2 mRNA vaccine. Issue 11 (3rd October 2021) - Gadi, Sanjay R. V.; Brunker, Patricia A. R.; Al‐Samkari, Hanny; Sykes, David B.; Saff, Rebecca R.; Lo, Janet; Bendapudi, Pavan; Leaf, David E.; Leaf, Rebecca Karp
Abstract: Background: Large clinical trials have demonstrated the overall safety of vaccines for severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2). However, reports have emerged of autoimmune phenomena, including vaccine‐associated myocarditis, immune thrombocytopenia, and immune thrombotic thrombocytopenia. Case Presentation: Here we present a novel case of a young woman who developed life‐threatening autoimmune hemolytic anemia (AIHA) after her first dose of a SARS‐CoV‐2 mRNA vaccine. Notably, initial direct antiglobulin testing was negative using standard anti‐IgG reagents, which are "blind" to certain immunoglobulin (IgG) isotypes. Further testing using an antiglobulin reagent that detects all IgG isotypes was strongly positive and confirmed the diagnosis of AIHA. The patient required transfusion with 13 units of red blood cells, as well as treatment with corticosteroids, rituximab, mycophenolate mofetil, and immune globulin. Conclusion: As efforts to administer SARS‐CoV‐2 vaccines continue globally, clinicians must be aware of potential autoimmune sequelae of these therapies.